Drummer Hoff - Emberley, Barbara; Emberley, Ed (New York : Simon and Schuster Books for Young Readers, 1987)
A cumulative folk song in which seven soldiers build a magnificent cannon, but Drummer Hoff fires it off.
"The Caldecott medal."--Cover.
Keywords: Folk songs -- Texts; Folk songs; Caldecott Medal